1987
DOI: 10.1039/dt9870000747
|View full text |Cite
|
Sign up to set email alerts
|

The chemistry of trichloro[tris(trimethylsilyl)methyl] and trichloro[tris(dimethylphenylsilyl)methyl] complexes of gallium, indium, and thallium. Crystal and molecular structures of [Li(thf)2(µ-Cl)2GaCl-{C(SiMe2Ph)3}]·thf, [Li(thf)3(µ-Cl)InCl2{C(SiMe3)3}], and [{(Me3Si)3C}In(µ-Cl)2{µ-Fe(CO)4}ln{C(SiMe3)3}](thf = tetrahydrofuran)

Abstract: The Chemistry of Trichloro[tris(trimethylsilyl)methyl] and Trichloro[t ris( dimethyl phenylsi lyl)methyl] Complexes of Gallium, Indium, and Thallium. Crystal and Molecular Structures of [Li(thf ),(pCI),GaCl-{ C (S i M e,Ph ),}]at hf, [ Li (thf ), ( p-CI ) InCI,{ C( Si Me3),}], and [{( Me,Si),C}ln(p-CI),{p-Fe(CO),)In{C(SiMe,),}] (thf = tetrahydrofuran) t

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…In contrast to the well-developed chemistry of (organo) group-13 halides X 3 - a ER a ( X = halide; R = alkyl, aryl) with carbonylmetal monoanions only very few reports on the related reactivity toward dianions exist. Noteworthy are some reports on indium and thallium transition metal compounds with special bonding situations, e.g., metallacumulenes and M−In(I) donor−acceptor interactions. For the lighter homologues, e.g., gallium, we recently communicated the dianionic “iniden” complexes {[(CO) n M] 2 (μ-GaR} 2- (M = Fe, n = 4, R = Me; M = Cr, n = 5, R = Me, Et), the monoanionic complexes {(CO) n M−Ga(X 1 X 2 (L)} - (M = Cr, Fe; n = 4, 5; X 1 = X 2 = Cl; X 1 = Cl, X 2 = Me, Et) and {(CO) n M−Ga[(CH 2 ) 3 NMe 2 ](X)} - (M = Cr, Mn, Fe; L = NO, CO; n = 3, 4; X = Cl, Me, t Bu) as well as the neutral complexes (CO) 4 Fe{Ga[(CH 2 ) 3 NMe 2 ](R)} 2 (R = t Bu, Ph) and {(CO) 4 Fe−Ga[(CH 2 ) 3 NMe 2 ]} 2 …”
Section: Resultsmentioning
confidence: 99%
“…In contrast to the well-developed chemistry of (organo) group-13 halides X 3 - a ER a ( X = halide; R = alkyl, aryl) with carbonylmetal monoanions only very few reports on the related reactivity toward dianions exist. Noteworthy are some reports on indium and thallium transition metal compounds with special bonding situations, e.g., metallacumulenes and M−In(I) donor−acceptor interactions. For the lighter homologues, e.g., gallium, we recently communicated the dianionic “iniden” complexes {[(CO) n M] 2 (μ-GaR} 2- (M = Fe, n = 4, R = Me; M = Cr, n = 5, R = Me, Et), the monoanionic complexes {(CO) n M−Ga(X 1 X 2 (L)} - (M = Cr, Fe; n = 4, 5; X 1 = X 2 = Cl; X 1 = Cl, X 2 = Me, Et) and {(CO) n M−Ga[(CH 2 ) 3 NMe 2 ](X)} - (M = Cr, Mn, Fe; L = NO, CO; n = 3, 4; X = Cl, Me, t Bu) as well as the neutral complexes (CO) 4 Fe{Ga[(CH 2 ) 3 NMe 2 ](R)} 2 (R = t Bu, Ph) and {(CO) 4 Fe−Ga[(CH 2 ) 3 NMe 2 ]} 2 …”
Section: Resultsmentioning
confidence: 99%
“…2) is related to that of 2 but it exits as an ''-ate'' complex with a distorted tetrahedral indium centre with one terminal bromide and two bromides that bridge to the lithium centre. This can be compared to [{(Me 3 Si) 3 C}InCl 2 (l-Cl)Li(THF) 3 ] [15], though in that case there is only one bridging halide. The In-C bond length of 2.176 (6) A in 3 is similar to those in related 4-coordinate complexes, e.g., 2.…”
Section: Triptycenyl Group 13 Halide Complexesmentioning
confidence: 98%
“…Use of the first of these methods is often complicated by the complexation of LiCl. [32][33][34] During our investigations into the use of di-tert-butylgallium dithiocarbamates, ( t Bu) 2 Ga(S 2 CNR 2 ), as precursors for the MOCVD growth of GaS, 35 we observed that if the reaction of [( t Bu) 2 Ga(µ-Cl)] 2 with Li(S 2 CN i Pr 2 ) was carried out in the presence of isopropanol (used to clean glassware!) the heterometallic chloride, of ( t Bu) 2 Ga(µ-Cl) 2 -Li(HO i Pr) 2 (10) was formed in low yield (see Experimental section) which was characterized by X-ray crystallography.…”
Section: Chloridementioning
confidence: 99%